simplify
![(1 - i \sqrt{3} )^{3} \times ( \sqrt{3} + i) ^{2} (1 - i \sqrt{3} )^{3} \times ( \sqrt{3} + i) ^{2}](https://tex.z-dn.net/?f=%281+-+i+%5Csqrt%7B3%7D+%29%5E%7B3%7D++%5Ctimes+%28+%5Csqrt%7B3%7D+++%2B+i%29++%5E%7B2%7D+)
Answers
Answered by
1
Answer:
Step-by-step explanation:(1^3-3√3i^3+9i^2) (3+i^2+2√3i)
=(1-3√3i^2.i-3√3i+9i^2) (3-1+2√3i)
=(1+3√3i-3√3i-9) (2+2√3i)
=(1-9) (2+2√3i)
=(-8) (2+2√3i)
=-16-16√3i Solved.
Similar questions
World Languages,
6 months ago
Chemistry,
6 months ago
Sociology,
6 months ago
Social Sciences,
1 year ago
Math,
1 year ago
Geography,
1 year ago
Chemistry,
1 year ago
Science,
1 year ago